Optimalisasi Pengelolaan Keuangan Perusahaan Konsultan Teknik (Studi Kasus CV. Citra Stapaka Sejahtera) - Alfi Azhari, Nourmala; Lisnawanty, Lisnawanty; Ardiyansyah, Ardiyansyah; Irmayani, Windi (Jurnal Sistem Informasi Akuntansi, 2023)
Financial data management at an engineering consulting company, namely CV. Citra Stapaka Sejahtera, currently uses Microsoft Excel. The observation results show that the management of financial data is still simple, resulting in a long time for presenting financial report information, less efficient processes, and errors that often occur in financial report information. To overcome this problem, this research aims to develop a financial management application using the prototype method. The system developed allows Admins and Leaders to access various features such as managing project master data, income and expenses, carrying out transactions, and producing various reports such as project reports, RAB, income, expenses and profit and loss, both for projects and general. The hope is that the implementation of this system can improve financial management performance at CV. Image of Stapaka Sejahtera.